Highly Active and Stable Single Atom Rh1/CeO2 Catalyst for CO Oxidation during Redox Cycling. Issue 1 (4th January 2023) - García‐Vargas, Carlos E.; Pereira‐Hernández, Xavier Isidro; Jiang, Dong; Alcala, Ryan; DeLaRiva, Andrew T.; Datye, Abhaya; Wang, Yong
Abstract: We report a single atom Rh1 /CeO2 catalyst prepared by the high temperature (800 °C) atom trapping (AT) method which is stable under both oxidative and reductive conditions. Infrared spectroscopic and electron microscopy characterization revealed the presence of exclusively ionic Rh species. These ionic Rh species are stable even under reducing conditions (CO at 300 °C) due to the strong interaction between Rh and CeO2 achieved by the AT method, leading to high and reproducible CO oxidation activity regardless of whether the catalyst is reduced or oxidized. In contrast, ionic Rh species in catalysts synthesized by a conventional impregnation approach (e. g., calcined at 350 °C) can be readily reduced to form Rh nanoclusters/nanoparticles, which are easily oxidized under oxidative conditions, leading to loss of catalytic performance. The single atom Rh1 /CeO2 catalysts synthesized by the AT method do not exhibit changes during redox cycling hence are promising catalysts for emission control where redox cycling is encountered, and severe oxidation (fuel cut) leads to loss of performance. Abstract : Active and Stable Catalysts for CO Oxidation : Rh1 /CeO2 prepared by high temperature calcination (800 °C) atom trapping (AT) method is stable for CO Oxidation regardless being subjected to Oxidative/Reductive treatments relevant for emission control. Infrared spectroscopy, Electron Microscopy and Temperature‐Programmed Reactions revealed stronger interaction between Rh and CeO2 in AT catalyst than in conventionally synthesized Rh/CeO2 (Calcined at 350 °C).